PENGARUH PENGGUNAAN AIR KOLAM TERHADAP KUAT TEKAN BETON (Studi Kasus Kecamatan. Kateman, Keritang dan Tembilahan Kota) - Muhammad Juldin; Akbar Alfa (Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir Riau, 2020)
AbstractConcrete is a composite material (mixture) consisting of cement, coarse aggregates, fine aggregates and water. The concrete formation mixture is designed in such a way as to produce fresh concrete that is easy to work with and meets the plan's compressive strength after hardening.The cement used is PCC type cement, although the composition of cement in concrete is only about 10%, but the role of cement is very important in concrete. Aggregates are mineral granules originating from nature or artificial which have a function as a mixture of fillers in concrete. The aggregate of the concrete mixture filler is divided into fine aggregates used from Javanese Inhu and coarse aggregates from Tanjung Balai Karimun. The fine aggregate is usually in the form of sand that passes through a filter with a diameter of 4.75 mm or 5 mm, while coarse aggregates do not pass through the filter. The water used is well water from Kateman District, Keritang District and Tembilahan District, Indragiri Hilir Regency, Riau Province.The compressive strength of concrete is the amount of load per unit area which causes the concrete specimen to break and there is no more carrying capacity. The average compressive strength of 28 days of cube specimens with well water in Kateman District = 491 kg / cm2, Keritang District = 469 kg / cm2 and Tembilahan District City = 475 kg / cm2. AbstrakBeton merupakan bahan komposit (campuran) yang terdiri dari semen, agregat kasar, agregat halus dan air. Campuran bahan-bahan pembentukan beton dirancang sedemikian rupa, sehingga menghasilkan beton segar yang mudah dikerjakan dan memenuhi kekuatan tekan rencana setelah mengeras.Semen yang digunakan adalah semen tipe PCC, walaupun komposisi semen dalam beton hanya sekitar 10%, namun peran semen sangat penting dalam beton. Agregat adalah butiran mineral yang berasal dari alam atau buatan yang memiliki fungsi sebagai bahan pengisi campuran pada beton. Agregat pengisi campuran beton terbagi atas agregat halus yang digunakan berasal dari Japura Inhu dan agregat kasar berasal dari Tanjung Balai Karimun. Agregat halus biasanya berupa pasir yang lolos saringan dengan diameter 4,75 mm atau 5 mm, sedangkan agregat kasar tidak lolos saringan tersebut. Air yang digunakan yakni air sumur berasal dari Kecamatan Kateman, Kecamatan Keritang dan Kecamatan Tembilahan Kota Kabupaten Indragiri Hilir Provinsi Riau.Kuat tekan beton adalah besarnya beban per satuan luas yang menyebabkan benda uji beton pecah dan tidak ada lagi daya dukungnya. Hasil kuat tekan rata-rata umur 28 hari benda uji kubus dengan air sumur Kecamatan Kateman = 491 kg/ cm2, Kecamatan Keritang = 469 kg/cm2dan Kecamatan Tembilahan Kota = 475 kg/cm2.